Removal of Tetracycline and the Degradation Products by Lemna gibba L. Exposed to Secondary Effluents - Topal, Murat; Senel, Gulsad Uslu; Obek, Erdal; Topal, E. Isil Arslan (Wiley, 2015)
The aims of this study were the determina (i) tetracycline CT(7.) and the degradation products removal efficiency of Elazig' Munictpal II'Istewater Treatment Plant (ii) the removal of TC and the degradation products in a pilot scale constructed wetland reactor planted with Lem na gibba L., which takes the effluent of the treatment plant (iii) the comparison of the removal of TC and the degradation products in the treatment plant and pilot scale reactor and (iv) the contribution of the planted u -ector to the treatment plant in terms of removal of TC and the degradation products. For these aims, composite samples were taken front both the influent and effluent of the treatment plant and the pilot scale reactor and then 7C and degradation products analyses were done by UPLC/ILS-111S. 7r 4,-epianhydroletacycline (1ATC) and anhydmtetracycline (ATC) removal efficiencies of the treatment plant were determined as 79.65, 64.42, and 80.19'4 respectively. 4-epitetracycline (ETC) removal efficienc) was not seen. TC; ETC, EATc and ATC removal efficiencies in the planted reactor were obtained as 55.4Z 89.85, 39.31 and 63. 427), respectively. The data obtained fu 010 the results of the analyses were also evaluated statistically. As a result, it was seen that Lenzna gibba L. was efficient to t-emove TC and the degradation products and improved the treatment plant IC and the degradation products removal efficiency. (C) 2015 American institute of Chemicat.Engineers Los iron Ping, 34: 1311-1321, 2015
Keywords: Lemna gibba L.; tetracycline; degradation product; UFLC-MS/MS; Turkey